The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.5435/jaaosglobal-d-23-00033
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Tibial Bone Defects: A Multicenter Experience of Hexapod and Ilizarov Frames

Abstract: Introduction: Bone defects may be managed with bone transport or acute shortening and lengthening using circular external fixation devices. We performed a multicenter retrospective cohort study to compare the outcomes between the Ilizarov frames and hexapod frames for the management of bone defects. Methods: Patients treated for bone defects using either Ilizarov or hexapod frames were included for analysis in two specialist institutions. Primary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Recent studies show that software‐assisted hexapod systems are more precise and/or easier to use in complex multiplanar deformities 25–28 . A thorough comparison of TSF with conventional Ilizarov ring fixator in the treatment of different types and severity of lower‐limb bone deformities has revealed that the automated TSF system is much more precise and less prone to posttreatment malalignment 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies show that software‐assisted hexapod systems are more precise and/or easier to use in complex multiplanar deformities 25–28 . A thorough comparison of TSF with conventional Ilizarov ring fixator in the treatment of different types and severity of lower‐limb bone deformities has revealed that the automated TSF system is much more precise and less prone to posttreatment malalignment 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that software-assisted hexapod systems are more precise and/or easier to use in complex multiplanar deformities. [25][26][27][28] A thorough comparison of TSF with conventional Ilizarov ring fixator in the treatment of different types and severity of lower-limb bone deformities has revealed that the automated TSF system is much more precise and less prone to posttreatment malalignment. 29 It also noted that the usage of software-assisted systems such as TSF and the one presented here require much less clinical experience compared to the Ilizarov ring fixator.…”
Section: Simulation Of Lambda Fixatormentioning
confidence: 99%